MINI WORKSHOP SEBAGAI UPAYA PENINGKATAN PROFESIONALITAS GURU DALAM MENYUSUN PERANGKAT PEMBELAJARAN DI SDN DADAPSARI - Churotin, Ainul (Persatuan Guru Republik Indonesia Kota Semarang, 2021)
The phenomenon that occurs in the teachers of SDN Dadapsari Korsatpen North Semarang, Semarang City, the number of subject matter requires teachers to compete to spend the target material so that they pay less attention to learning devices that should be their duties. of the 15 teachers, there are 10 or 67% of teachers who have not achieved the competence, while the remaining 5 teachers or 33% of teachers have achieved the desired competence. Teachers have not been able to compile learning tools because teachers do not understand how to arrange good learning tools. This is where the importance of supervision from the principal to the teacher by conducting mini workshops. This study is intended to answer the following problems: 1) How is the implementation of a mini workshop to improve teacher professionalism in compiling learning tools at SDN Dadapsari Korsatpen Semarang Utara, Semarang city for the 2020/2021 academic year?. 2) Is there an increase in teacher professionalism in compiling learning tools after a mini workshop was held at SDN Dadapsari Korsatpen North Semarang, Semarang city in the 2020/2021 academic year?. These problems are discussed through classroom action research which is carried out through 2 cycles with each cycle the stages are planning, action, observation and reflection. The results showed that: 1) The implementation of a mini workshop to improve teacher professionalism in compiling learning tools at SDN Dadapsari Korsatpen North Semarang, Semarang city in the 2020/2021 academic year was carried out by providing material to teachers on how to develop good learning tools, giving examples of reels, inviting the teacher to practice and discuss preparing a good device and the results are discussed together and the results of the learning tools carried out by the teacher are assessed and if errors are found, they are corrected. 2) The implementation of mini workshops can increase the professionalism of teachers at SDN Dadapsari Korsatpen North Semarang, Semarang City in the 2020/2021 academic year in compiling learning tools, this can be seen from the increase in the results of teacher professionalism in classroom administration management per cycle where in the first cycle there are 10 teachers or 67 % and in the second cycle there were 14 students or 93%. These results indicate that these results are in line with expectations. An increase also occurred in teacher activities in participating in mini workshops where in the first cycle there were 11 students or 77% and in the second cycle there were 14 students or 93%. The increase is the implementation of mini workshops to be one effective way for school principals in improving the ability of teachers in preparing learning tools